The impact of Crisis Intervention Team Training for police - Hassell, Kimberly D. (International journal of police science & management, 2020)
Policing persons with mental illness and/or emotional/behavioral issues is complex and difficult. Police interactions and encounters of this nature are expected to increase due to dwindling budgets and the resulting deficiencies of local mental health systems. Police departments are responding to this growing need by requiring officers to attend Crisis Intervention Team (CIT) Training. CIT Training is designed to teach officers about mental illness and effective strategies and techniques for engaging and de-escalating potentially volatile interactions and encounters. This study was conducted in a large, Midwestern, municipal police department. The data were triangulated and included: (a) CIT Training pre- and post-tests administered to officers (N=323) prior to and upon completion of the required 40-hour CIT Training held during the months of October through December 2016 and February through May 2017; (b) participant observation with police patrol officers in three of the seven police districts (N=127 hours; April 2017 through May 2017); (c) semi-structured interviews with police patrol officers assigned to three of the seven police districts who had completed the CIT Training (N=32 patrol officers; intensive interviews were conducted during participant observation); (d) in-person semi-structured interviews with service providers/practitioners who interact with officers in the context of their working roles and responsibilities (N=27; July 2017 through January 2018); and (e) interviews with Urbantown Police Department (UPD) executive command staff, CIT coordinators and UPD telecommunications personnel (N=10; September 2017 through January 2018). The assessment finds that the CIT Training administered in a large, municipal police department changed officers’ perceptions, as well as their street-level practices with persons with mental illness and/or emotional/behavioral issues. This assessment also finds that police officers are taking fewer persons into custody for involuntary treatment, and are instead transporting more persons for voluntary treatment.